2010
DOI: 10.4238/vol9-4gmr851
|View full text |Cite
|
Sign up to set email alerts
|

Soybean physiology and gene expression during drought

Abstract: ABSTRACT. Soybean genotypes MG/BR46 (Conquista) and BR16, drought-tolerant and -sensitive, respectively, were compared in terms of morphophysiological and gene-expression responses to water stress during two stages of development. Gene-expression analysis showed differential responses in Gmdreb1a and Gmpip1b mRNA expression within 30 days of water-deficit initiation in MG/BR46 (Conquista) plants. Within 45 days of initiating stress, Gmp5cs and Gmpip1b had relatively higher expression. Initially, BR16 showed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
36
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 34 publications
5
36
0
3
Order By: Relevance
“…Water stress significantly reduced the total leaf area. Under stress, drought tolerant soybean cultivars exhibited a larger leaf area when compared with less tolerant cultivars (Moreira et al, 2010). Leaf area of ten soybean genotypes at different growth stages under non-stress and water stress environments showed significant differences (Table 3.).…”
Section: Leaf Areamentioning
confidence: 99%
“…Water stress significantly reduced the total leaf area. Under stress, drought tolerant soybean cultivars exhibited a larger leaf area when compared with less tolerant cultivars (Moreira et al, 2010). Leaf area of ten soybean genotypes at different growth stages under non-stress and water stress environments showed significant differences (Table 3.).…”
Section: Leaf Areamentioning
confidence: 99%
“…Environmental stresses such as drought can greatly damage crop production (Stolf-Moreira et al, 2010). Several researchers have conducted systematic research on the morphological, physiological, and molecular characteristics of drought-resistant plants (Nassar et al, 2010;Reis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Northern blot analysis revealed that NaCl stress caused a general induction of GmPAP3 expression in both roots and leaves of various cultivated (Glycine max) and wild (Glycine soja) soybean varieties (Liao et al, 2003). In another study, GmPAP3 gene expression was reported to have increased under drought stress in soybean (Zhu et al, 1998;Stolf-Moreira et al, 2010).…”
mentioning
confidence: 99%